2010
DOI: 10.1063/1.3435213
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization-assisted energy transport in light-harvesting complexes

Abstract: We study the role of the dimer structure of light-harvesting complex II (LH2) in excitation transfer from the LH2 [without a reaction center (RC)] to the LH1 (surrounding the RC) or from the LH2 to another LH2. The excited and unexcited states of a bacteriochlorophyll (BChl) are modeled by a quasispin. In the framework of quantum open system theory, we represent the excitation transfer as the total leakage of the LH2 system and then calculate the transfer efficiency and average transfer time. For different ini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 30 publications
2
63
0
Order By: Relevance
“…Our single atom array is an ideal platform for forming Rydberg rings, which have been analyzed theoretically recently in references [62][63][64]. Due to "Rydberg blockade" effect [6,7], this system is ideally suited to perform multi-qubit operations, investigate quantum phenomena in strong interactions and experimentally simulate the energy transport procedure in light-harvesting complexes [12]. Furthermore, based on the construction of the Lamb-Dicke trap, it is possible to further cool single atoms down to the motional ground state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our single atom array is an ideal platform for forming Rydberg rings, which have been analyzed theoretically recently in references [62][63][64]. Due to "Rydberg blockade" effect [6,7], this system is ideally suited to perform multi-qubit operations, investigate quantum phenomena in strong interactions and experimentally simulate the energy transport procedure in light-harvesting complexes [12]. Furthermore, based on the construction of the Lamb-Dicke trap, it is possible to further cool single atoms down to the motional ground state.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, single atom array can serve as a research platform for physical models described in other systems that are not directly investigated experimentally. The few-body simulation offers an opportunity to understand some intriguing many-body phenomena, such as superconductivity in solid materials [11], and the natural process of photosynthesis [12]. Instead of being adiabatically transferred from ultracold atomic ensemble, in our experiment single atom array is built one by one based on "collisional blockade" mechanism [13,14] that locks the atom number either zero or one in ultra small dipole trap in the presence of near-resonant laser light.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have attempted to unravel the precise role of quantum coherence in the EET of light-harvesting complexes [6][7][8][9][10][11][12][13][14][15]. The interplay of coherent dynamics, which leads to a delocalization of an initial excitation arriving at the FMO complex from the antenna, and the coupling to a vibronic environment with slow and fast fluctuations, has led to studies of environmentally assisted transport in the FMO.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments by G. S. Engel et al [6] and G. Panitchayangkoon et al [7] have shown that the electronic coherence between two excitonic levels at both cryogenic (77K) and ambient (300K) temperatures. These experimental studies have generated a lot of theoretical interests [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] in understanding the role of quantum coherence in light harvesting efficiency. In particular, M. Sarovar et al [25] present numerical evidences for the existence of entanglement in the FMO complex for relatively long times.…”
mentioning
confidence: 99%